2014
DOI: 10.1158/1078-0432.ccr-14-0424
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Cells via the Reactive Oxygen Species-Mediated Unfolded Protein Response with a Novel Synthetic Polyphenol Conjugate

Abstract: Purpose: The selective killing of tumor cells is an important strategy for cancer therapeutics. The aim of this study was to develop a novel antitumor agent that is safe for normal cells with the ability to selectively target cancer cells.Experimental Design: On the basis of quantitative structure-activity relationship, we synthesized a novel polyphenol conjugate (E)-3-(3,5-dimethoxyphenyl)-1-(2-methoxyphenyl)prop-2-en-1-one (DPP-23). We evaluated the effect of DPP-23 on proliferation, cell cycle, and apoptosi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 43 publications
(46 reference statements)
0
44
0
Order By: Relevance
“…3E). Our previous study has demonstrated that DPP-23 induces ROS production and triggers apoptosis through the unfolded protein response (UPR) in the ER (Shin et al 2014). Thus, it seems likely that HymnPro might stimulate ER stress-mediated apoptosis due to ROS accumulation in a manner similar to that of DPP-23.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3E). Our previous study has demonstrated that DPP-23 induces ROS production and triggers apoptosis through the unfolded protein response (UPR) in the ER (Shin et al 2014). Thus, it seems likely that HymnPro might stimulate ER stress-mediated apoptosis due to ROS accumulation in a manner similar to that of DPP-23.…”
Section: Resultsmentioning
confidence: 99%
“…Capan-1 cells were treated with 20 lM HymnPro for 24 or 48 h. Cellular DNA contents and propidium iodide (PI)-stained dead cells were analyzed by flow cytometry as previously described (Shin et al 2014). Fluorescence was measured with a FACSCalibur flow cytometer (BectonDickinson Immunocytometry Systems, San Jose, CA, USA).…”
Section: Cell Cycle and Cell Death Analysismentioning
confidence: 99%
See 3 more Smart Citations